1993
DOI: 10.1165/ajrcmb/9.3.279
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Cytokine Transcripts in the Bronchoalveolar Lavage Cells of Patients with Asthma

Abstract: A panel of steady-state cytokine mRNAs was analyzed in the bronchoalveolar lavage (BAL) cells from asthmatic subjects or patients challenged with ragweed allergen. This was achieved by combining both qualitative and quantitative assays using the reverse transcription-polymerase chain reaction (RT-PCR). Analysis of BAL cells from six mild allergic asthmatic and five nonasthmatic, nonallergic subjects showed no qualitative differences in the profile of cytokine mRNAs (including interleukin [IL]-1 beta, IL-2, IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
35
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(35 citation statements)
references
References 19 publications
0
35
0
Order By: Relevance
“…The intensity of IL-5 mRNAexpression correlated well with that of eosinophilic infiltration, whereas that of IL-3 and GM-CSF did not (12). Wehave reported that IL-5 production by CD4+T cells of asthmatic patients is significantly enhanced compared to that of healthy controls (13).…”
Section: Introductionmentioning
confidence: 65%
“…The intensity of IL-5 mRNAexpression correlated well with that of eosinophilic infiltration, whereas that of IL-3 and GM-CSF did not (12). Wehave reported that IL-5 production by CD4+T cells of asthmatic patients is significantly enhanced compared to that of healthy controls (13).…”
Section: Introductionmentioning
confidence: 65%
“…Increasing evidence places IL-5 in a key role in the development of eosinophilia in asthma (5,6). IL-5 mRNA was significantly enhanced in bronchoalveolar lavage cells obtained from asthmatics challenged with ragweed antigen (8). Again, peripheral blood T cells from asthmatics were found to secrete IL-5 in response to the common house dust mite (Dermatophagoides farinae) antigen (13).…”
mentioning
confidence: 96%
“…good evidence that in atopic asthmatics, a Th2-type response occurs in the airways (5)(6)(7)(8). Although it appears that the outcome of many diseases such as asthma is determined by the ratio of Th1 to Th2 cells (4), the molecular basis for Th1-and Th2-specific gene expression remains to be elucidated.…”
mentioning
confidence: 99%
“…The lung inflammatory responses in asthma are tightly associated with airway hyperresponsiveness, and Th2 cells play a critical role in initiating and sustaining asthmatic lung inflammation. In asthma patients, activated CD4 ϩ T cells with predominant Th2 type cytokine (IL-4 and IL-5) expression are present in bronchoalveolar lavage (BAL) fluid and in lung biopsies (2)(3)(4)(5). In murine models, the importance of CD4 ϩ Th2 cells in the development of pulmonary allergic inflammation has also been demonstrated.…”
mentioning
confidence: 99%